Crescimento, fotossíntese e partição de assimilados em genótipos de arroz irrigado - Falqueto, Antelmo Ralph (2008)
xii In this study, photosynthetic characteristics of irrigated rice (Oryza sativa L.) genotypes were evaluated. It were also evaluated with relation to growth and assimilates partitioning characteristics rice cultivars differing in yield potential, BRS Pelota (higher yield) and BRS Firmeza (lower yield). No correlation between maximum efficiency of PS2 photochemical (Fv/Fm) and year of release was observed among cultivars. However, between 1900-1960, a decline in effective efficiency of PS2 photochemistry (Fv /Fm ) and effective quantum yield of photochemical energy conversion (Ф PS2) was observed and their recover after 1960 was consistent with a higher yield potential. Differences in maximal O2 evolution rate also were expressive between genotypes, especially, in the sterile line IR58025A when compared to the normal fertility found in IR58025B line. In those rice cultivars differing in yield, the chlorophyll content was maintained by at least 15 days in BRS Firmeza (stay green phenotype), which reflected in the maintaining of Fv/Fm and Fs/Fo values. Significant reductions in chlorophyll content, Fv/Fm and Fs/Fo were clear only at grain filling stage, which showed significant differences between flag and the 2 nd , 3 th and 4 th leaves. Decreasing in the chlorophyll fluorescence parameters in ligh-adapted state (Fv /Fm ,Ф PS2 and photochemical quenching - q P ) also occurred and they were more clear mainly after the flowering stage in both cultivars. Their values were always higher in BRS Firmeza rice cultivar, reflecting the presence of stay green genes, which are responsible for a delay in leaf senescence. The Fs/Fo ratio values, a CO2 assimilatory capacity indicator, were positively correlated to Fv/Fm and Fv /Fm values and negatively correlated to q N (non-photochemical quenching). In relation to growth and assimilates partitioning characteristics, plants of the BRS Pelota rice cultivar showed higher total dry matter accumulated (Wt) at end of life cicle, higher leaf area (Af) and higher dry matter allocated toward culm + sheath and panicles. The yield component which presented higher relevance for yield was the panicle number. Thus, the higher grain yield of BRS Pelota could be related to a higher leaf area and leaf area duration, which permits the providing of elevated quantity of photoassimilates by higher period time.